Mengungkap Sistem Pemasaran Nasi Boran Dengan Pendekatan Teori Entrepreneurial Marketing - Muyassirah Muyassirah; Mohammad Arief (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This research aims to describe the appropriate marketing system for selling Nasi Boran with an entrepreneurial marketing theory approach. The research method used in this research is a qualitative method with a case study approach. Data mining techniques in this research, namely: observation, interviews, literature study, and documentation. Data reduction, data display (display), and verification used for analyzing data. The results of this study indicate that there are seven variables to the entrepreneurial marketing theory approach on the marketing of Nasi boran. These include: (1) Proactive, namely increased sales. (2) Innovative, which is creating new ideas. (3) Calculated Risk-Taking, namely facing the competitive world of business. (4) Opportunities, namely seeing and taking opportunities. (5) Customer Intensity, namely building and maintaining good relationships. (6) Resource Leveraging, namely using and utilizing existing resources. (7) Value Creation, namely creating new combinations.